2017
DOI: 10.1002/rnj.197
|View full text |Cite
|
Sign up to set email alerts
|

Deliberately Light Interpersonal Touch as an Aid to Balance Control in Neurologic Conditions

Abstract: Deliberately light IPT resembles a manual handling strategy, which minimizes load imposed on healthcare professionals when providing balance support, while it facilitates patients' own sensorimotor control of body balance during standing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…12,13 IPT reduces sway in patients with chronic stroke as well as Parkinson's disease. 14 More rostral IPT (at shoulder level) reduces sway to a greater amount than more caudal (low back) locations, 14 which is analogous to single-person effects of light touch on body sway. 15,16 The observation that more cranial IPT results in more reduced sway could be caused by a clearer signal due to greater sway amplitude at the contact point.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 IPT reduces sway in patients with chronic stroke as well as Parkinson's disease. 14 More rostral IPT (at shoulder level) reduces sway to a greater amount than more caudal (low back) locations, 14 which is analogous to single-person effects of light touch on body sway. 15,16 The observation that more cranial IPT results in more reduced sway could be caused by a clearer signal due to greater sway amplitude at the contact point.…”
Section: Discussionmentioning
confidence: 99%
“…The touch stabilization paradigm has been extended by Wing and Johanssen in a number of very imaginative ways of potential use for rehabilitation and fall prevention. They have shown that interpersonal touch at very low force levels can be helpful in stabilizing older people's posture and gait (25)(26)(27)(28)(29). Sawers and Ting have shown how small inter-person forces can be used to communicate goals and actions between individuals but also how they can be incorporated in the design of rehabilitation robots (30,31).…”
Section: Alternative Interpretationsmentioning
confidence: 99%
“…For example during balance exercises, this can lead to an allocation of sub-tasks, such as provision of haptic balance support by a therapist and reception by the client involved in the balancing task [9].…”
Section: Significancementioning
confidence: 99%
“…Johannsen et al [9] assessed "passive" IPT in neurological patients as well as chronic stroke and reported sway reductions between 15%-26%. In stroke patients, passive, trunk-based IPT [9], nevertheless, seemed more beneficial than fingertip IPT [16].…”
Section: Significancementioning
confidence: 99%